AN OVEVIEW OF FRUIT AND VEGETABLE SUPPLY CHAIN MODEL IN HANOI - Thi Thanh Huyen, Nguyen; Thi Anh Van, Nguyen (Journal of Forestry Science and Technology, 2020)
There are models of fruit and vegetable supply chains in Hanoi: Chain of participants, chain of wholesaler Mega Market, chain of retailers; Vineco closed chain and Sharefarm share chain. The model of the supply chain of vegetables and fruits by members (i.e. chains without leadering members) has many advantages: meeting up to 90% consumption of the market, a rich variety of fruits and vegetables, a wide distribution channels, throughout and affordable prices... but the quality and food safety are still inadequate. The other chain models have advantages: product quality and food safety are initially paid attention, but high prices; limited types, and the distribution channels are mainly in urban areas... During the operation, the models of fruit and vegetable supply chains have also faced many certain difficulties: (1) Compliance with commitments on quality and food safety is not serious; (2) Traditional market system has many weaknesses in management; (3) Chains lack monitoring mechanisms; (4) The dissemination and application of traceability code system (QR) is too slow... In order to increase the added value and increase the sustainability of the chains of chain leaders and industry managers, there must be a change in orientation, reorganization, and strengthening of monitoring mechanisms. string to suit living conditions and new requirements for quality standards.